Early-life exposure to aflatoxin B1 and associated effects on gut microbiota: preliminary results under earlyMYCO project - Silva, I. (2021)
Aflatoxin B1 (AFB1) produces acute or chronic deleterious health effects in humans and animals. Still, long-term effects derived from initial exposure in early life, a critical period for colonization and development of gut microbiota, has not been fully evaluated. Particularly, aflatoxins could impair gut microbiota and immunity settlement, as they have been proven to cross the placental barrier and can be found in breast milk. We investigated the impact of maternal exposure to AFB1 on early-life microbiota in a mouse model. Females were fed jelly pellets containing 400 µg/kg AFB1 diluted in DMSO (treated animals n=6) or DMSO vehicle alone (control group n=6) during pregnancy and lactation. Faeces from the offspring of both treated and control females were collected immediately after weaning and faecal DNA was extracted and purified. Bacterial taxa diversity and relative abundance were assessed by High-Throughput Sequencing performed in an Illumina Miseq® sequencer, targeting the V3 and V4 regions of the 16S rRNA gene. Operational taxonomic units (OTUs) were determined by clustering reads to 16S reference databases. A hundred and twenty-four (N=124) bacterial genera were found in both groups, 5 were only present in AFB1 treated group and 27 exclusively in control groups. A hundred and fifty-one (N=151) bacterial species were common to both groups, 15 species exclusively found in AFB1 litters and 34 species were exclusively found in control litters. To assess abundance and characterize species diversity and evenness, Shannon diversity index was calculated but no significant differences were found between groups. Although present in both groups, Akkermansia muciniphila and Bacteroides acidifaciens were significantly higher in controls. A. muciniphila colonizes the intestinal tract in childhood and regulates mucus thickness, intestinal barrier integrity and is involved in immune modulation. B. acidifaciens participates in the metabolism of lipids and sugars and activates some cytokines and immune cell receptors. Sulfidogenic bacteria recently related to inflammatory bowel disease such as Desulfovibrio piger and Bilophila wadsworthia were exclusivly found in the treated litters. Early-life gut microbiome is paramount to trigger the gut immune defences, but is far less stable than the adult microbiome. Moreover, previous work identified aflatoxins intake as a potential health hazard in Portuguese children. These preliminary results open an extensive field to further investigate the association between mycotoxins and microbiome, as the latest is increasingly recognized as a major player in a wide spectrum of diseases.